Parlamentskii chas . Parlamentskii chas . Parliamentary Hour . Парламентский час - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Withdrawal of old banknotes from circulation in Russia; discussion of the outcomes of the All-Russian economic conference. Featured in the program: Vartazarova, Liudmila (Doctor of Economic Sciences); Ispravnikov, Vladimir (Deputy Chairman of the Supreme Council of the Russian Federation); Khandruev, Aleksandr Andreevich (Deputy Head of the Central Bank of the Russian Federation); Miliukov, Anatolii Illarionovich (Doctor of Economic Sciences) Изъятие денежных купюр старого образца в России; обсуждение итогов Всероссийского экономического совещания. В программе участвуют: Вартазарова, Людмила (Доктор экономических наук); Исправников, Владимир (Заместитель председателя Верховного Совета Российской Федерации); Хандруев, Александр Андреевич (Заместитель председателя Центрального банка Российской Федерации); Милюков, Анатолий Илларионович (Доктор экономических наук)